2008
DOI: 10.1007/bf03043987
|View full text |Cite
|
Sign up to set email alerts
|

Environmental changes and diversification ofCyprideis in the Late Miocene of the Styrian Basin (Lake Pannon, Austria)

Abstract: ~e turnover from the Sarmatian Paratethys Sea into Lake Pannon around 11.6 Ma seriously impacted aquatic biota like ostracods and triggered their adaptation to the changed environments. One survivor of this ecological switch is certainly the genus Cyprideis, which is well known for its radiation in Lake Pannon. A high-resolution micropalaeontological investigation of a transgressive-regressive sedimentary cycle just above the Middle/Late Miocene boundary focused on the taxonomy of the found Cyprideis species. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
7

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 29 publications
2
30
0
7
Order By: Relevance
“…It is a typical euryhaline species (Boomer & Eisenhauer 2002;Rostovtseva & Tesakova 2009). Similar observations and discussion about environmental changes and diversification of Late Miocene Cyprideis from the Lower Pannonian of the Styrian Basin have been reported by Gross (2008) and Gross et al (2008). Analogous forms of Amnicythere species are living in the sublittoral zones of the Black Sea and the Caspian Sea in brackish environments as well as in more freshwater bays (Cziczer et al 2009).…”
Section: Discussionsupporting
confidence: 77%
“…It is a typical euryhaline species (Boomer & Eisenhauer 2002;Rostovtseva & Tesakova 2009). Similar observations and discussion about environmental changes and diversification of Late Miocene Cyprideis from the Lower Pannonian of the Styrian Basin have been reported by Gross (2008) and Gross et al (2008). Analogous forms of Amnicythere species are living in the sublittoral zones of the Black Sea and the Caspian Sea in brackish environments as well as in more freshwater bays (Cziczer et al 2009).…”
Section: Discussionsupporting
confidence: 77%
“…This was also the case for research carried out by Gross et al (2008), who demonstrated that Cyprideis species from Lake Pannon (Austria) with strong resemblance to each other could be separated only by applying elaborate morphometric techniques. The citation of the species named Cyprideis torosa in stratigraphical and/or palaeoecological studies of Miocene and, by extension, Pliocene, Quaternary and Recent ostracods, must therefore be interpreted with some caution, certainly when the species is only listed, and not described or figured.…”
Section: Originmentioning
confidence: 89%
“…This indicates that in a single population there may be specimens with and without a spine, illustrating that the presence of such a spine is perhaps a less important diagnostic feature of C. torosa than is generally accepted. Gross et al (2008) disagree with this point of view and consider the number of spines as a valuable feature for species discrimination. This may well be the case for the three Cyprideis species mentioned in their paper, but not for C. torosa.…”
Section: Originmentioning
confidence: 93%
“…in recent years, ostracod researchers seem leaning towards using the computer program Morphomatica, based on a B-spline algorithm specifically adapted to ostracod valve outline (Baltanás et al 2003;linhart et al 2006), which provides valuable results in specific discrimination (i.a., iepure et al 2007;ligios & Gliozzi 2012;Mazzini et al 2014). The method has been described, for example, in Gross et al 2008. This technique has been used mostly on smooth or weakly ornamented ostracod taxa, whereas we tested its effectiveness by using it to discriminate strongly reticulated forms.…”
Section: Outline Analysismentioning
confidence: 99%